2021
DOI: 10.31234/osf.io/f7rwv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Threat learning impairs subsequent memory recombination with past episodes

Abstract: To successfully predict important events, the representations in memory on which we rely need to be constantly updated and transformed to best reflect a complex and dynamic world. Here we employed a novel paradigm to investigate how memories of threat learning affect the flexible recombination across distinct but overlapping experiences, an ability referred to as relational memory. Participants (n=35) visited the lab to first encode neutral associations (A - B), which were reactivated and predictively associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The episodic conditioning paradigm enables the direct presentation of many stimulus pairs that trigger strong CRs and URs in healthy participants, which can be related to the presence of declarative memory associations. As another example of how this paradigm can be used to integrate ideas from Pavlovian threat conditioning and episodic memory, one study from our lab used this paradigm to investigate whether threat affects the ability to draw connections between distinct memories through a shared element, also known as associative inference (de Vries et al, 2021). We found that associative inference was impaired by threat, but that this effect was not moderated by intensity of emotional responses to the USs.…”
Section: Discussionmentioning
confidence: 95%
“…The episodic conditioning paradigm enables the direct presentation of many stimulus pairs that trigger strong CRs and URs in healthy participants, which can be related to the presence of declarative memory associations. As another example of how this paradigm can be used to integrate ideas from Pavlovian threat conditioning and episodic memory, one study from our lab used this paradigm to investigate whether threat affects the ability to draw connections between distinct memories through a shared element, also known as associative inference (de Vries et al, 2021). We found that associative inference was impaired by threat, but that this effect was not moderated by intensity of emotional responses to the USs.…”
Section: Discussionmentioning
confidence: 95%
“…Simply increasing the intensity of the here-employed electric stimulus would be unethical, but a multimodal aversive stimulus as US could be an option to further enhance the motivational effects of conditioning. A multimodal US could be composed of an image and a corresponding sound (e.g., sound of snapping celery--image of badly broken leg) and thereby emulate a real-life, multimodal experience that amplifies the impact of a stimulus (de Vries et al, 2021). These stimuli do not pose a direct threat to the participant, but have been shown to be perceived as highly aversive and evoke a very strong physiological defensive responses (de Vries et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A multimodal US could be composed of an image and a corresponding sound (e.g., sound of snapping celery--image of badly broken leg) and thereby emulate a real-life, multimodal experience that amplifies the impact of a stimulus (de Vries et al, 2021). These stimuli do not pose a direct threat to the participant, but have been shown to be perceived as highly aversive and evoke a very strong physiological defensive responses (de Vries et al, 2021). In the present study, we merely assessed whether a Pavlovian CS would elicit conditioned suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Simply increasing the intensity of the here-employed electric stimulus would be unethical, but a multi-modal aversive stimulus as US could be an option to further enhance the motivational effects of aversive conditioning. A multimodal US could be composed of an image and a corresponding sound (e.g., sound of snapping celery -image of badly broken leg) and thereby emulate a real-life, multi-modal experience that amplifies the impact of a stimulus (Vries, Grasman, Kindt, & Ast, 2021). These stimuli do not pose a direct threat to the participant, but have been shown to be perceived as highly aversive and evoke a very strong physiological defensive responses (Vries et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A multimodal US could be composed of an image and a corresponding sound (e.g., sound of snapping celery -image of badly broken leg) and thereby emulate a real-life, multi-modal experience that amplifies the impact of a stimulus (Vries, Grasman, Kindt, & Ast, 2021). These stimuli do not pose a direct threat to the participant, but have been shown to be perceived as highly aversive and evoke a very strong physiological defensive responses (Vries et al, 2021). In the present study, we merely assessed whether a Pavlovian CS would elicit conditioned suppression.…”
Section: Discussionmentioning
confidence: 99%